Hydrodynamic interactions between ships in narrow channels - Paulauskas, Vytautas; Paulauskas, Donatas; Maksimavičius, Ričardas; Jonkus, Martynas (Transport, 2014)
Hydrodynamic interactions between ships in narrow channels are important for studying purposes and practical tasks. The paper presents a theoretical basis for the interaction between ships in narrow channels to evaluate reciprocal actions between ships, the experimental results of real ships and data received applying calibrated simulators. The theory and experimental results displayed in the paper could be used for designing channels and evaluating navigational safety in narrow channels as well as for ship steering tasks in narrow channels.